Implementasi Pembelajaran Berbasis Literasi Digital dalam Menguatkan Moderasi Beragama bagi Siswa di SMP Negeri 1 Pademawu - Nailatur Rizqiyah; Masti Yanto; Waqi’atul Masrurah (Jurnal Ilmiah Literasi Indonesia, 2025)
The purpose of this study is to determine the application of digital literacy-based learning in strengthening religious moderation for students at SMP Negeri 1 Pademawu. The background of this study is the existence of intolerant cases that still occur in Indonesia, even in school environments. In addition, this study is also motivated by the development of technology that has positive and negative impacts, so that literacy becomes important for generation Z to dive into the virtual world while still upholding religious teachings that have moderate values. This study uses a qualitative approach with a descriptive type, with data collection techniques using interviews and documentation. Meanwhile, the results of this study can be concluded that the form of application of digital literacy-based learning at SMP Negeri 1 Pademawu is by utilizing social media (WhatsApp, YouTube) and using media in the form of projectors in delivering learning materials. In terms of instilling the value of religious moderation in students, educators at the institution use social media in the form of YouTube to share content about attitudes of tolerance between religious communities.